Development of a social learning theory-based pressure injury training program for nursing assistants in Chinese nursing homes - Guo, Yanxia; Yang, Shengnan; Boonyamalik, Plernpit; Powwattana, Arpaporn; Zhu, Wen; Xu, Lingxia (Frontiers in Public Health, 2025)
IntroductionPressure injury (PI) is a significant concern in Chinese nursing homes, particularly in China, especially due to the rapidly aging population. Nursing assistants play a vital role in PI prevention and management but often lack adequate training. To address this gap, we developed a training program for nursing assistants based on Social Learning Theory (SLT), aimed at improving their competencies in PI prevention and management. The modified Delphi method was used to gather expert consensus on the program’s structure and content.MethodsA two-round Delphi process was performed involving an expert panel in wound care, community nursing, geriatric nursing, and nursing education. The training program was designed based on SLT, emphasizing observational learning, enactive learning, and behavioral reinforcement. Several experts evaluated the training program’s content, which was informed by systematic reviews and qualitative interviews with stakeholders. Data analysis included expert’s positive coefficient, expert’s authority coefficient (Cr), expert’s coordination coefficient (Kendall’s W), and coefficient of variation (CV) were used to reflect reliability and consensus.ResultsConsensus was reached on 79 key indicators for the training program, which included 4 first-level indicators (training objectives, content, methods, and evaluation), 13 second-level indicators, and 62 third-level indicators. The expert authority coefficient was 0.93, and Kendall’s W values of 0.372 (p < 0.001) in the first round and 0.177 (p < 0.001) in the second round indicated strong agreement among experts. The program integrates SLT principles, such as attention, retention, motor reproduction, and motivation, to enhance the training’s effectiveness.ConclusionThe study developed a comprehensive SLT-based PI training program for nursing assistants in Chinese nursing homes using the modified Delphi method. The program addresses the critical need for competency-based training in PI prevention and management. Future research should focus on the implementation and evaluation of this program in real-world settings to determine its effectiveness in improving nursing assistants’ skills and reducing PI incidence among older adult residents.